(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
This article addresses the pedagogical itinerary of the Extensionist Rondon Nucleus of the State University of Santa Catarina - NER/UDESC, bringing aspects of epistemological understanding, considering the choices for curriculum that provide integration between society and university, in which the knowledge and demands of these spaces dialogue from the perspective of access to what is necessary for an emancipated and emancipatory society, as a political practice, in which choices can be intentionally directed towards the common good. KEYWORDS: University Extension. NER/UDESC. Social Immersion.